2004
DOI: 10.1038/sj.bjc.6602098
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antiproliferative mechanisms by RB24, a targeted precursor of multiple inhibitors of epidermal growth factor receptor and a DNA alkylating agent in the A431 epidermal carcinoma of the vulva cell line

Abstract: Recently, with the purpose of enhancing the potency of epidermal growth factor receptor (EGFR)-based therapies, we designed a novel strategy termed 'Cascade-release targeting' that seeks to develop molecules capable of degrading to multiple tyrosine kinase (TK) inhibitors and highly reactive electrophiles, in a stepwise fashion. Here we report on the first prototype of this model, RB24, a masked methyltriazene, that in addition to being an inhibitor on its own was designed to degrade to RB14, ZR08, RB10 þ a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Here, we describe a similar strategy based on the use of a small-molecule approach to target EGFR or Her2 TK-mediated signaling pathways while damaging DNA. This strategy, termed "combi-targeting," seeks to design a single molecule targeted to the TK function of Her2 or EGFR and programmed to be a latent DNA-damaging agent (Matheson et al, 2001(Matheson et al, , 2003(Matheson et al, , 2004aBrahimi et al, 2002Brahimi et al, , 2004Banerjee et al, 2003Banerjee et al, , 2004Rachid et al, 2003;Qiu et al, 2004).…”
mentioning
confidence: 99%
“…Here, we describe a similar strategy based on the use of a small-molecule approach to target EGFR or Her2 TK-mediated signaling pathways while damaging DNA. This strategy, termed "combi-targeting," seeks to design a single molecule targeted to the TK function of Her2 or EGFR and programmed to be a latent DNA-damaging agent (Matheson et al, 2001(Matheson et al, , 2003(Matheson et al, , 2004aBrahimi et al, 2002Brahimi et al, , 2004Banerjee et al, 2003Banerjee et al, , 2004Rachid et al, 2003;Qiu et al, 2004).…”
mentioning
confidence: 99%
“…Combi-molecules such as SMA41 and RB24 have been shown to block EGFR and to methylate DNA (7,27). Although numerous studies from our group have confirmed the dual actions of combi-molecules (7)(8)(9), little is known about the optimal condition under which they exhibit their optimal potency.…”
Section: Discussionmentioning
confidence: 99%
“…1). This type of molecules RB24 [21,22] or RB107 [23] showed half-lives in the 45 minute range. With the purpose of enhancing the bioavailability of combi-molecules of the triazene class, we recently sought to further stabilize them by synthesizing a series of quinazoline-based 1,2,3-triazenes containing a hydrolabile carbamate at the 3-position of the triazene chain [24].…”
Section: Introductionmentioning
confidence: 95%
“…We recently developed a novel strategy termed "combitargeting" [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][29] that seeks to design molecules designated as "combi-molecules", capable of not only blocking the tyrosine kinase activity of EGFR, but also damaging the DNA of the cells, thereby conferring cytotoxic properties to these inhibitors. At the advanced stages, many solid tumours including breast, prostate and lung carcinomas overexpress EGFR, a receptor that in many cases activate the PI3K-Akt pathway, thereby leading to resistance to apoptosis [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation